2020
DOI: 10.1111/ppa.13149
|View full text |Cite
|
Sign up to set email alerts
|

Plant genotype and temperature impact simultaneous biotic and abiotic stress‐related gene expression in Pythium‐infected plants

Abstract: Under changing climate, plants need combined ability to cope with co‐occurring biotic/abiotic stresses. Understanding simultaneous plant responses to multiple stresses offers unique insights towards developing effective strategies to mitigate effects of such stresses in plants. Quantitative reverse transcription PCR was used to determine and compare relative gene expression ratios (RGERs) of three disease resistance‐related genes, chalcone synthase, GA protein, and phenylalanine ammonia lyase (PAL), and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…Climate change made not only abiotic stresses but also biotic stresses more challenging for plant scientists. Often, fluctuations in temperature or water stress directly trigger biotic stressors' negative response and do irreversible damage to the plants [132,133]. The positive roles of HD-ZIP genes in mitigating abiotic stresses have been discussed above.…”
Section: Role Of Hd-zip Gene Family In Regulating Biotic Stressmentioning
confidence: 99%
“…Climate change made not only abiotic stresses but also biotic stresses more challenging for plant scientists. Often, fluctuations in temperature or water stress directly trigger biotic stressors' negative response and do irreversible damage to the plants [132,133]. The positive roles of HD-ZIP genes in mitigating abiotic stresses have been discussed above.…”
Section: Role Of Hd-zip Gene Family In Regulating Biotic Stressmentioning
confidence: 99%
“…The results support the view that a reduction to a single genotype would not have provided transferable data, as major differences between the genotypes became visible. Other studies with combined stress also came to this conclusion [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 64%
“…Experiments with combined biotic and abiotic stresses considering multiple genotypes are very rare but show an influence of the genotypes used. When combining temperature stress and Pythium infection in three Trifolium genotypes, You et al [ 16 ] found that the genotypes used also influenced the results. In up to 51 soybean genotypes, Grinnan et al [ 17 ] observed a strong effect of the genotype on the outcome of the combined stresses of drought and insect herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that the combined effects of abiotic and biotic factors on yield have rarely been studied and are usually related to investigations in controlled conditions [ 18 , 22 ], this study examined potentials of regression models to explain yield loss in barley as a result of plant response to combinatorial stressors. Our results indicated that only combining abiotic and biotic predictor variables into the same regression model would give higher potentials for yield loss predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Lamichhane [ 17 ] indicated that re-evaluation of the routine-based planting of pesticide seed treatment is needed from economic, environmental, and social points of view, although planting pesticide-treated seeds was proven to be an important practice for the control of seed-borne and soil-borne diseases. You et al [ 18 ] also indicated that the effectiveness of fungicides against individual soil-borne pathogens can differ from their effectiveness against soil-borne pathogen complexes. Since there is little knowledge on the patterns of joined occurrence of U. nuda and P. graminea in barley production areas and their effect on barley yield loss under fluctuating climatic conditions, the aim of this study was to investigate how joined occurrence of U. nuda and P. graminea affects barley yield, and whether fluctuating climatic conditions affect control of these pathogens.…”
Section: Introductionmentioning
confidence: 99%